Outcomes of nonsurgical endodontic treatment under general anesthesia in special health care needs: An observational study - Fahd Alsalleeh; Fatima Y. Albishry; Asrar S. Aleyiydi; Farah S. Aldossari; Norah H. Alharbi; Maha Alghofaily; Riyadh Althumairy (Nature Publishing Group, 2024)
Abstract Background and aim The alarming rise in the number of people with special health care needs (SHCNs) necessitates a paradigm shift in how to approach their oral health needs. General anesthesia (GA) is a valuable technique for facilitating dental procedures in patients with SHCNs who may not be able to tolerate treatment without it. The aim was to assess nonsurgical endodontic treatment and outcomes in patients with SHCNs performed under GA. Method Seventy-eight permanent teeth in 33 patients who received nonsurgical endodontic treatment under GA were included between 2018 and 2022 in SHCNs hospital clinics. The demographic data, types of SHCNs, pulpal and periapical diagnosis, type of treatment, and material used were analyzed. All patients were recalled for clinical and radiographic examinations. Pre-treatment and recall periapical radiographs were evaluated and scored using the Periapical Index (PAI). Results Autism and Attention deficit hyperactivity disorder were 39.4% of patients treated. Most treatments delivered were primary nonsurgical root canal treatment (95%). Warm vertical compaction of gutta-percha for obturation accounted for 88% of cases treated. Single cone obturation technique was used in 9 cases (12%) utilizing tricalcium silicate sealer. At the recall visits, 98.7% of teeth treated had survived. Twelve teeth have pre-treatment periapical lesions, and all healed except one. Female patients were found to have higher scores of PAI compared to male patients (23.7% vs 7.5%), yet insignificant. Only 10 patients with nonsurgical root canal treatment reported recurrent caries. Conclusion This study demonstrates a high survival rate for nonsurgical endodontic treatment performed under GA in a cohort of patients with SHCNs. Interestingly, patients with social and communication disorders received the highest proportion of treatments under GA. These findings highlight the potential of GA-facilitated endodontics for this population. However, further research is warranted to explore additional methods for optimizing oral health outcomes in SHCNs.